Evaluation of the Efficacy of Single Anastomosis Sleeve Ileal (SASI) Bypass for Patients with Morbid Obesity: a Multicenter Study - Mahdy, T (2020)
Background: Single anastomosis sleeve ileal (SASI) bypass is a newly introduced bariatric and metabolic procedure. The present multicenter study aimed to evaluate the efficacy of the SASI bypass in the treatment of patients with morbid obesity and the metabolic syndrome. Methods: This is a retrospective, seven-country, multicenter study on patients with morbid obesity who underwent the SASI bypass. Data regarding patients' demographics, body mass index (BMI), percentage of total weight loss (%TWL), percentage of excess weight loss (%EWL), and improvement in comorbidities at 12 months postoperatively and postoperative complications were collected. Results: Among 605 patients who underwent the SASI, 54 were excluded and 551 (390; 70.8% female) were included. At 12 months after the SASI, a significant decrease in the BMI was observed (43.2 ± 12.5 to 31.2 ± 9.7 kg/m2; p < 0.0001). The %TWL was 27.4 ± 13.4 and the %EWL was 63.9 ± 29.5. Among the 279 patients with type 2 diabetes mellitus (T2DM), complete remission was recorded in 234 (83.9%) patients and partial improvement in 43 (15.4%) patients. Eighty-six (36.1%) patients with hypertension, 104 (65%) patients with hyperlipidemia, 37 (57.8%) patients with sleep apnea, and 70 (92.1%) patients with GERD achieved remission. Fifty-six (10.1%) complications and 2 (0.3%) mortalities were recorded. Most complications were minor. All patients had 12 months follow-up. Conclusions: The SASI bypass is an effective bariatric and metabolic surgery that achieved satisfactory weight loss and improvement in medical comorbidities, including T2DM, hypertension, sleep apnea, and GERD, with a low complication rate.